Esiselvitys yhteiskunnallisesta yrittämisestä: Katsaua yhteiskunnallisiin yrityksiin ja vaikuttavuusinvestoimiseen Suomessa; Overview of Social Enterprises and Impact Investment in Finland - Annu Kotiranta; Joona Widgrén (The Research Institute of the Finnish Economy (ETLA), 2015)
– The aim of this report has been to produce an analysis of the state of the social enterprises in Finland. Based on a comprehensive survey, there are roughly 19 000 social enterprises in Finland that employ around 125 000 persons. These estimates produced in this report multiply the views on the magnitude of the phenomenon. Self-identified Finnish social enterprises produce social value though their products or services and mostly in the field of social services and welfare. The main hindrances on the way of the growth of the sector are the lack of an unambiguous definition of a social enterprise and the shortages in measuring the most important outcome, social impact. Measuring and valuing the impact is a key element in attracting funding for social enterprises. New means of impact investment attract not only attention but also capital that seeks for targets, especially in Europe. This additional funding is a much needed in the sector that attracts it's outside financing currently mostly from public sector and struggles to find financing critical for future growth.
Keywords: L38; L26; N34; P13; G23; G24; M14; G11; G14; 330; Social enterprises; Impact investment; Sozialwirtschaft; Corporate Social Responsibility; Nachhaltige Kapitalanlage; Finnland